SME Finance in Africa - Beck, Thorsten; Cull, Robert (World Bank Group, Washington, DC, 2014)
This paper uses cross-country firm-level surveys to gauge access to financial services and the importance of financing constraints for African enterprises. The paper compares access to finance in Africa and other developing regions of the world, within Africa across countries, and across different groups of firms. It relates firms' access to finance to firm and banking system characteristics and discusses policy challenges.